Simplicity of Faith, Intuition and Giordano Bruno: Nicolas Steno’s Florentine Diary and his Philosophy Lessons with Ferdinando III de’ Medici. New Insights from BNCF, Gal. 291 - Sobiech, Frank (Kirkehistoriske Samlinger, 2016)
Intet resumé.